Math Algebra

Resolve(17x²+14x + 9) – (-13x² +6x - 12)

30xsquared+20x+21

I'll try to be helpful and show the work. This is the method I learned last quarter.
(17x"sq"+14x+9)
+ (13x"sq"+6x+12)
=
(30X"sq"+20x+21)
I used the vertical method but the step are the same either way.

Step 1: Remove parentheses
Step 2: Combine like terms
Step 3: Simplify

I hoped I helped. Polynomials can be rather simple if you know the short cuts.
oh, and if you use the vertical method, don't forget to change the signs. When subtracting a negative it becomes adding a positive.

could you help me with this problem? y=3(x+5)(x-2)...the answer is supposed to be y=3xsquared+ 9x-30...how did they get the -30

  1. 👍 0
  2. 👎 0
  3. 👁 234

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Prove 3(x+1)(x+7)-(2x+5)² is never positive So, 3(x+1)(x+7)-(2x+5)(2x+5) =3(x²+8x+7)-(4x²+20x+25) =3x²+24x+21-4x²-20x-25 =-x²+4x-4

  2. Math

    solve the equation 20x^3 +44x^2 -17x -5 given that -5/2 is a zero of f(x) 20x^3 +44x^2 -17x -5 I used synthetic division and got 20x^2-6x-2=0 took 2 and divided it out of that equation 2(x+5/2)=10x^2 -3x-1 then i factored it out

  3. 10th Maths ch-polynomials

    Obtain all zeros of f(x)= x3 + 13x2 + 32x + 20, if one of it's zero is -2

  4. Algebra 2

    The function f(x) = -5x. The graph of g(x) is f(x) vertically compressed by a factor of 1/4 and reflected in the x axis. What is the function rule for g(x)? g(x) = -20x g(x) = -5/4x g(x) = 20x g(x) = 5/4x I think it's B, but I'm

  1. Biology

    1aOrder the following steps of microscope use. A. Observe the specimen under low power; resolve with the fine adjustment. B. Raise the stage; observe under scanning power; focus with coarse adjustment; resolve with fine

  2. math help pls pls pls

    Given f(x) = 4x + 13 and g(x) = 10x − 2, solve for (f + g)(x) and select the correct answer below. (f + g)(x) = 14x + 15 (f + g)(x) = 14x + 11 (f + g)(x) = 6x + 11 (f + g)(x) = 6x + 15 is it b pls help me

  3. Maths

    find the equation of the perpendicular bisector of the line joining P(2, -4) to Q(-5,1) A. 8y-14x 13=0 B. 8y-14x-13=0 C. 8y 14x-13=0 D. 8y 14x 13=0 Please I need someone to help me with this, with an explanatory workings.

  4. math

    Simplify the given equation. 17x - 6 + 3x - 5 = x + 11 + 4x A)20x - 11 = 5x + 11 B)20x + 1 = 5x + 11 C)9x = 16x

  1. algebra

    15. f(x) = -13x2 + 12x + 14 g(x) = 11x - 13 find f(g(7)) g(7) = 11(7) -13 = 64 f(g(7)) = f(64) = -13(64)^2 + 12(64) + 14 = -52,466 is this correct?

  2. algebra

    Which equation is the standard form of −56x+14x^2=−51? 14x^2−56x+51=0 14x^2+51−56x=0 −56x+14x^2−51=0 14x^2−56x−51=0 I do believe it is A or D, is one of these correct?

  3. polynomials

    (3+7x)-(16x2+15x2) (3+1x)-(12x+16+0+18x2) Q4: (15+13x2+14x2)+(13x+18x) Q5: (2x2+1+15x2+7+3)+(0x+17x) Q6: (18x+3)+(17x2+1x2+9+8+0x) Q7: (6x + 14) - (9x + 5) Q8: (14x2 + 13x + 12) - (7x2 + 20x + 4) Q9: Subtract -10x2 + 16x - 15 from

  4. math

    which equation is equivalent to 5x-2(7x+1)=14x? why? a -9x-2=14x b -9xt1=14x c -9x+2=14x d 12x-1=14x

You can view more similar questions or ask a new question.